Speech Acts on Discourse Analysis Used in a Speech “What Really Matters at the End Life” by BJ Miller - Popiana Br Hutauruk; Jesana Tessalonika Simaremare; Astrinia Ristama Tampubolon; Albert Welman Daulat Lumbangaol; David Suranta Sinamo; Herman Herman (Journal of English Language and Education, 2023)
This study aims to analyze and identify the contents of the speech "What Really Matters at the End of Life" by BJ Miller. The subject of this research is the script of the speech "What Really Matters at the End of Life" by BJ Miller. We analyze and examine each script of the speech "What really matters at the end of life?" by BJ Miller to make it easier to understand as a sample of speech acts in the speech "What really matters at the end of life?" by BJ Miller. Later, the results of the speech act data in the speech "What Really Matters at the End of Life" by BJ Miller will be reviewed to further identify and categorize the types of speech acts. We used a qualitative method with realistic analysis results in this study. We have analyzed a speech with the title "What Really Matters at the End of Life?" by BJ Miller and found several types of speech acts that often appear in each verse of the speech script, namely declarations, representatives, expressives, directives, and the last one, commissives. The dominant speech act in the script of the speech "What really matters at the end of life?" by BJ Miller is representation